Cerveja artesanal: Um estudo de caso da produção, comercialização e consumo em Fortaleza - Cavalcante, Arthuro Magno Moreira (2021)
We start, for our research, from the following question: how is the production of craft beer in the city of Fortaleza? Thus, we researched the production in a brewery in Ceará and we hypothesized that this market has been expanding in this city and that its production is similar, in some aspects, to the production of large breweries. The theoretical framework was prepared based on the authors Morado (2017); Dragone, Silva and Silva (2016) and Breda (2016). For its accomplishment, field research was used with the use of technical visits and semi-structured interviews; the method was exploratory research, in addition to involving a bibliographic survey, interviews and a descriptive method. The interview with the brewery's collaborator allowed us to corroborate some facts found in the literature, such as the production time being compatible between the industry and the small brewery, in addition to offering the result that the brewery in question was in the process of expansion before the Covid-19 pandemic and that he managed to maintain this process even during the period of social isolation maintained in the city.